Nicaea and Women’s Ordained Ministry - Munkholt Christensen, Maria Louise (The ecumenical review, 2025)
Looking to the forthcoming Sixth World Conference on Faith and Order, we might recollect that the fifth conference at Santiago de Compostela in 1993 spoke of “continuing our study” on the ordination of women, but this ambition has never been carried out. The 1700th anniversary of the Council of Nicaea offers an opportunity to revisit how the council dealt with the issue of the ordination of women, in particular as deaconesses. This article argues that although the canons of Nicaea reflect a general male-centred orientation of ecclesial authority, one of the canons reveals a more complex picture, in which deaconesses – though ambiguously situated – were at least present and acknowledged. The anniversary of Nicaea invites us to acknowledge the historical presence and liturgical roles of ordained women in the early church and celebrate the ministry of women not only as a past reality but as a living tradition that still calls for discernment and renewal today.